Raising Awareness of Sleep as a Healthy Behavior - Geraldine S. Perry, DrPH, RDN; Susheel P. Patil, MD, PhD; Letitia R. Presley-Cantrell, PhD (Centers for Disease Control and Prevention, 2013)
Sleep is an essential component of health, and its timing, duration, and quality are critical determinants of health (1). Sleep may play an important role in metabolic regulation, emotion regulation, performance, memory consolidation, brain recuperation processes, and learning (2). Because of the importance of these functions, sleep should be viewed as being as critical to health as diet and physical activity. However, public health practitioners and other health care providers have not focused major attention on the importance of sleep to health. In this essay, we briefly summarize the scientific literature about hours of sleep needed and why sleep is an important public health issue. We also suggest areas for expanding sleep research and strategies for increasing awareness of the importance of sleep and improving sleep health. Finally, we call for action to bring sleep to the forefront of public health.